2019
DOI: 10.1101/623728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-trait genome-wide association meta-analysis of dietary intake identifies new loci and genetic and functional links with metabolic traits

Abstract: Dietary intake, a major contributor to the global obesity epidemic 1-5 , is a complex phenotype partially affected by innate physiological processes. [6][7][8][9][10][11] However, previous genome-wide association studies (GWAS) have only implicated a few loci in variability of dietary composition. 12-14 Here, we present a multi-trait genome-wide association meta-analysis of inter-individual variation in dietary intake in 283,119 European-ancestry participants from UK Biobank and CHARGE consortium, and identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Strong associations also appeared when genetic polymorphisms in the NEGR1 gene were linked with dietary intake [ 13 , 14 ] and with psychological features generally associated with eating disorders [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Strong associations also appeared when genetic polymorphisms in the NEGR1 gene were linked with dietary intake [ 13 , 14 ] and with psychological features generally associated with eating disorders [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genomic locus of FTO gene, also known as alpha-ketoglutarate dependent dioxygenase, has been strongly associated with BMI and obesity [ 51 ]. Besides significant associations with AUD and alcohol consumption phenotypes [ 4 , 5 , 8 ], FTO also appears to be one of the most important loci associated with food intake [ 52 ] suggesting that FTO gene could be a pleiotropic locus that has impact on common reward pathways implicated in the excess consumption of both food and alcohol. Indeed, it has been shown that FTO participates in the regulation of D2R-dependent reward learning and modulates the connectivity in a basic reward circuit of meso-striato-prefrontal regions [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…5-9 Five genomewide association studies (GWAS) of macronutrient intake have been conducted to date; the most recent multi-trait analysis identified 96 independent genetic loci by combining summary statistics of individual macronutrient GWAS from 24-hour diet recall questionnaires in 283K individuals in UK Biobank (UKB). 6-10 In addition, the Neale Lab conducted GWAS (http://www.nealelab.is/uk-biobank/) across thousands of mostly binary traits analyzed primarily as dichotomous outcomes (i.e. wholemeal bread vs. all others) in 361K unrelated individuals in UKB.…”
mentioning
confidence: 99%